SISTEM PENJUALAN GAS LPG 3KG BERBASIS RFID DENGAN MEMANFAATKAN e-KTP - Septiadiz Rodin; Elva Pebrina; Muhammad Iqbal Nugraha; Yudhi Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The scarcity of LPG for the size of 3 kilograms (3KG subsidized LPG) is caused by the implementation of government regulations regarding subsidized 3KG LPG in the field. To overcome these problems, a 3KG LPG gas sales system was designed by utilizing e-KTP as a condition for purchase transactions. This system works by reading the ID of each customer's e-KTP using an RFID reader sensor MFRC522. NodeMCU ESP8266 is used as a microcontroller as well as a wifi module so that the device can connect to the internet network. The website-based application is implemented as a system portal and a place to store customer data. The features provided in the application include recording and checking customer ID and recapitulation of 3KG LPG sales transactions in real time. Customer ID recording is done by entering the name, NIK and address, accompanied by an edit feature if there is a change or update of customer data. The results obtained from the experiment show that the RFID reader sensor can detect e-KTP well at a maximum distance of 0.5 CM with the e-KTP position parallel to the RFID reader. KTP and transactions are limited to 3 purchases per month e-KTP ID.